Lack of association between rs1024611 (-2581 A/G) polymorphism in CC-chemokine Ligand 2 and susceptibility to pulmonary Tuberculosis in Zahedan, Southeast Iran - Naderi, M; Hashemi, M; Karami, H; Moazeni-Roodi, A; Sharifi-Mood, B; Kouhpayeh, H; Taheri, M; Ghavami, S (Prague medical report, 2011)
Approximately 5-10% of subjects infected with Mycobacterium tuberculosis develop active tuberculosis. It has been proposed that genetic factors determine the host's vulnerability to tuberculosis. Chemokine (C-C motif) ligand 2 (CCL2), commonly known as monocyte chemoattractant protein-1 (MCP-1), plays a key role in protective immunity against M. tuberculosis. The present study was aimed to determine if there was an association between -2581 A/G single nucleotide polymorphism of CCL2 and pulmonary tuberculosis (PTB) in a sample of Iranian subjects. This case-control study was performed on 142 PTB and 166 healthy subjects. The polymorphism of CCL2 (rs1024611) was determined using tetra amplification refractory mutational system-polymerase chain reaction (tetra ARMS-PCR). There were no significant differences between PTB patients and control subjects regarding -2581 A/G single nucleotide polymorphism of CCL2. In conclusion, our results do not support an association of -2581 A/G polymorphism of CCL2 with PTB susceptibility.
Keywords: Polymorphism, Single Nucleotide; Humans; plicní tuberkulóza; lidé středního věku; Iran; jednonukleotidový polymorfismus; Female; frekvence genu; lidé; chemokin CCL2; Írán; ženské pohlaví; Male; Middle Aged; Chemokine CCL2; Genetic Predisposition to Disease; genetická predispozice k nemoci; Tuberculosis, Pulmonary; Gene Frequency; mužské pohlaví